Assessing patient PREFERence between the dulaglutide pen and the semaglutide pen: A crossover study (PREFER). Issue 3 (19th December 2019) - Matza, Louis S.; Boye, Kristina S.; Stewart, Katie D.; Coyne, Karin S.; Wullenweber, Paula K.; Cutts, Katelyn N.; Jordan, Jessica B.; Wang, Qianqian; Yu, Maria; Currie, Brooke M.; Malley, Karen G.; Ishak, K. Jack; et al.
Abstract: Aim: When selecting treatments for type 2 diabetes (T2D), it is important to consider not only efficacy and safety, but also other treatment attributes that have an impact on patient preference. The objective of this study was to examine preference between injection devices used for two weekly GLP‐1 receptor agonists. Materials and Methods: The PREFER study was an open‐label, multicentre, randomized, crossover study assessing patient preference for dulaglutide and semaglutide injection devices among injection‐naïve patients receiving oral medication for type 2 diabetes. After being trained to use each device, participants performed all steps of injection preparation and administered mock injections into an injection pad. Time‐to‐train (TTT) for each device was assessed in a subset. Results: There were 310 evaluable participants (48.4% female; mean age, 60.0 years; 78 participants in the TTT subgroup). More participants preferred the dulaglutide device than the semaglutide device (84.2% vs. 12.3%; P  < 0.0001). More participants perceived the dulaglutide device to have greater ease of use (86.8% vs. 6.8%; P  < 0.0001). After preparing and using the devices, more participants were willing to use the dulaglutide device (93.5%) than the semaglutide device (45.8%). Training participants to use the dulaglutide device required less time than the semaglutide device (3.38 vs. 8.14 minutes; P  < 0.0001). Conclusions: Participants with type 2 diabetes preferred the dulaglutide injection device to the semaglutide injection device. If patients prefer a device, they may be more willing to use the medication, which could result in better health outcomes. Furthermore, a shorter training time for injection devices may be helpful in busy clinical practice settings.